2004
DOI: 10.1016/j.febslet.2004.03.096
|View full text |Cite
|
Sign up to set email alerts
|

The effect of phalloidin and jasplakinolide on the flexibility and thermal stability of actin filaments

Abstract: In this work the effect of phalloidin and jasplakinolide on the dynamic properties and thermal stability of actin filaments was studied. Temperature dependent fluorescence resonance energy transfer measurements showed that filaments of Ca-actin became more rigid in the presence of phalloidin or jasplakinolide. Differential scanning calorimetric data implied that the stiffer filaments also had greater thermal stability in the presence of phalloidin or jasplakinolide. The fluorescence and calorimetric measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
50
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 23 publications
8
50
0
Order By: Relevance
“…JAS markedly inhibited virion infection, whereas actin destabilizers did not. The variable effects of these actin-targeted drugs suggested either that JAS induced a structural barrier to endocytosis through the stabilization of the cortical actin cytoskeleton or that these late endocytic steps required actin filament turnover, which is inhibited by JAS (Bubb et al, 2000;Visegrady et al, 2004) but not always by CD (Cooper, 1987). Our results are consistent with both of these interpretations.…”
Section: The Role(s) Of Actin In Hemoglobin Transportsupporting
confidence: 82%
“…JAS markedly inhibited virion infection, whereas actin destabilizers did not. The variable effects of these actin-targeted drugs suggested either that JAS induced a structural barrier to endocytosis through the stabilization of the cortical actin cytoskeleton or that these late endocytic steps required actin filament turnover, which is inhibited by JAS (Bubb et al, 2000;Visegrady et al, 2004) but not always by CD (Cooper, 1987). Our results are consistent with both of these interpretations.…”
Section: The Role(s) Of Actin In Hemoglobin Transportsupporting
confidence: 82%
“…A similar shift in the melting temperature of F-actin was previously observed by Nikolaeva et al [25]. In agreement with previous results the presence of jasplakinolide has shifted the T m to 87.3 °C [10]. We also found that when the jasplakinolide bound to the ADP.BeF x saturated actin filaments the melting temperature shifted to 85.6 °C, i.e.…”
Section: Introductionsupporting
confidence: 81%
“…This toxin can decrease the amount of sequestered actin monomers by lowering the critical concentration of actin and enhances the polymerization of the filaments by accelerating the speed of the nucleation step [13]. Differential scanning calorimetry (DSC) studies revealed that jasplakinolide is able to stabilize actin filaments at sub-stoichiometric concentration as well [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the binding of phalloidin stabilizes the structure of actin filaments (27)(28)(29)(30)(31)(32)(33) and one bound phalloidin can stabilize seven neighboring protomers (26). In this work, we characterize the effect of phalloidin on the thermal stability of actin filaments in complex with different nucleotide analogues (ADP.BeF x or ADP.AlF 4 ) by using differential scanning calorimetry (DSC).…”
mentioning
confidence: 99%